IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH APHORISMS - Ahmedova Gulizebo Yakubovna (Web of Journals Publishing, 2024)
The learning of vocabulary is an important part in foreign language learning. Vocabulary is considered as central in language teaching and is of paramount importance to a language learner. Improving vocabulary skill among English language learners is a challenge faced by many teachers. The objective of the article is to find out the way in improving students’ vocabulary skill through aphorisms.
Keywords: aphorisms, vocabulary, foreign language learning, memory, aspects, spoken and written language, principles.